Glycolic Acid Oxidase Activity in Cell-free Preparations of Blue-Green Algae - Grodzinski, B. (1970)
Glycolic acid oxidase activity was detected in cell-free preparations of Anabaena flos-aquae and Oscillatoria sp. by the reduction of 2,6-dichlorophenolindophenol and by the formation of glyoxylate. Enzyme activity was localized in the 20,000 times gravity supernatant fraction, and optimal activity was obtained at pH 8.0. Activity was lost on storing the preparation at 4 C and could not be restored by addition of flavin mononucleotide. Oxidase activity of the supernatant fraction of Oscillatoria sp. was slightly stimulated by addition of flavin mononucleotide, but that of A. flos-aquae was unaffected by addition of this cofactor. The formation of glyoxylate by supernatant fractions of either alga was markedly inhibited by the addition of α-hydroxysulfonates.